2015
DOI: 10.1080/07373937.2015.1052502
|View full text |Cite
|
Sign up to set email alerts
|

Moisture conditioning of wood using a continuous microwave dryer

Abstract: Lower moisture content in wood, preferably 5-6%, is desirable for many chemical modification reactions. Economically it is not feasible to dry timber to such low moisture content by conventional drying without drying degrades. Microwave heating was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Reduction in moisture content compared to untreated groups found by [45]. Sethy et al [47] pointed out that drying the wood until 5% or 6% MC is not economically reasonable using conventional drying methods without causing undesirable drying problems. According to the authors, wood elements with lower MC need to be chemically modified.…”
Section: Wood Dryingmentioning
confidence: 96%
See 1 more Smart Citation
“…Reduction in moisture content compared to untreated groups found by [45]. Sethy et al [47] pointed out that drying the wood until 5% or 6% MC is not economically reasonable using conventional drying methods without causing undesirable drying problems. According to the authors, wood elements with lower MC need to be chemically modified.…”
Section: Wood Dryingmentioning
confidence: 96%
“…As stated by other authors [23,38,40], the drying was uniform within the specimens, generating fewer drying defects. The authors also suggested that MW technology may be used for this purpose in a reduced period and that further investigations using different wood species and dimensions are necessary [47].…”
Section: Wood Dryingmentioning
confidence: 99%
“…Microwave (MW) wood modification is an environmentally friendly modification technique with relatively low energy consumption [15] when compared to some other modification techniques, and supports various wood processing operations by significantly improving permeability, treatability, and uptake of wood preservatives [16][17][18][19][20][21][22]. Microwave treatment of wood is particularly useful for less permeable wood, as in this way we can improve the impregnability of the wood and achieve more effective protection to increase its resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave modification is an eco-friendly technique that reduces energy consumption (Sethy et al 2016) and aids in several wood processing operations such as seasoning and preservative treatment by significantly improving wood's permeability and preservative uptake, resulting in its effective use for a longer period in service. Previous research on microwave (MW) showed a positive impact on retention and penetration of wood pertaining to moderate and high refractory index with different chemicals and catalysts (Samani et al 2019, Ganguly and Tripathi 2018, Vinden et al 2017, Terziev and Daniel 2013, Sethy et al 2012, Dashti et al 2012, Torgovnikov and Vinden 2009.…”
Section: Introductionmentioning
confidence: 99%